System vibration control using linear quadratic regulator - Abdelrahman, Mostafa; Aryassov, Gennady; Tamre, Mart; Penkov, Igor (Zielona Góra: Uniwersytet Zielonogórski)
Balancing a bipedal robot movement against external perturbations is considered a challenging and complex topic. This paper discusses how the vibration caused by external disturbance has been tackled by a Linear Quadratic Regulator, which aims to provide optimal control to the system. A simulation was conducted on MATLAB in order to prove the concept. Results have shown that the linear quadratic regulator was successful in stabilizing the system efficiently.
Keywords: linear quadratic regulator; inverted pendulum on cart